Taurolidine Peritoneal Dialysis Catheter Lock to Treat Relapsing Peritoneal Dialysis Peritonitis - Alvarez Nadal, Marta (Kidney Med, 2020)
Peritonitis remains a primary challenge for the long-term success of peritoneal dialysis (PD) technique and one of the main reasons for catheter removal. Prevention and treatment of catheter-related infections are major concerns to avoid peritonitis. The use of taurolidine catheter-locking solution to avoid the development of a biofilm in the catheter’s lumen has obtained good results in hemodialysis catheters for reducing infection rates, although there is scarce literature available regarding its utility in PD. We describe the case of a woman in her 60s who developed relapsing peritonitis due to Pseudomonas aeruginosa, with no possibility of removing peritoneal dialysis catheter because she was not a suitable candidate for hemodialysis. After the fourth peritonitis episode caused by Pseudomonas species, the use of taurolidine catheter-locking solution was initiated. She received a total of 9 doses, with a favorable microbiological and clinical outcome and no further relapses more than 10 months after taurolidine PD catheter lock treatment was started. We report the successful elimination of an aggressive bacteria after taurolidine PD catheter lock use, with no relevant adverse events.